An assessment of public consultation strategies in South African infrastructure projects: a case of the Gauteng Freeway Improvement Projects (GFIP) - Peter, Mzwandile (My University, 2021)
There is a growing concern about the implementation of public infrastructure projects in South Africa. Most public projects in South Africa are plagued with public resistance, and the implication of this public resistance has dire consequences to the economy. The Gauteng Freeway Improvement Projects (GFIP) is one example of a public project that has faced unprecedented public resistance from various stakeholders including trade unions, civil society actors and citizens due to the failure of the Gauteng Provincial government to adhere to public consultation prior to the implementation of the project. There is therefore a need to assess the consultative regimen in public service infrastructure projects in South Africa. The aim of the study is to assess the inclusiveness and transparency of public consultation processes in South Africa prior to the implementation of public infrastructure projects. The study used GFIP as a case study to assess public consultation strategies in South African infrastructure projects. The study made use of the interviews as a tool for collecting primary data. Data was collected from individuals whose organisations were involved in the GFIP and have working knowledge of the GFIP and the e-tolling system. The main fining of the study is that South African government failure in implementing public infrastructure projects is exacerbated by the one size fit all approach by government when engaging with the public. Government must move away from the approach by providing service to the communities, government must use public participation to understand what the community requirements are. The study further suggest that public participation must be an iterative design process throughout the various stages of the life cycle of the project
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Building (in the field of Project Management in Construction), 2021